Customer service and how it affects the satisfaction of account holders a study of Shahjalal Islami Bank Limited, College gate branch - Momen, MD Moksudul (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.